522 Aspergillus Niger: an Unusual Cause of Invasive Pulmonary Aspergillosis. (October 2012) - Hammami, S; Haddad, S; Lajmi, K; Brahim, N Bel Hadj; Ghédira, L; Meriem, C Ben; Guediche, MN
Abstract : Objective: Report two cases of chronic granulomatous disease presenting with uncommon cause of invasive pulmonary aspergillosis (IPA). Methods: We report two cases of IPA in two 6-year-old twin girls with a family history of primary immunodeficiency and a personal medical history of recurrent bronchopneumopathy referred to our Pediatric Department in July 2011 for investigations regarding persistent pneumonia and biological inflammatory syndrome. IPA was confirmed by isolating Aspergillus niger from bronchoalveolar lavage and radiology results. Amphotericin B therapy was initiated intravenously for 1 month relayed then by oral Voriconazole for two months. Clinico-biological evolution was favourable. Follow-up computed tomography showed full regression of the pulmonary infiltrates and the thoracic wall mass after 3 months of antifungal therapy. Investigation for immune deficiency revealed chronic granulomatous disease. Our two patients started then on prophylactic antibiotics with co-trimoxazole. We are currently considering HLA identical bone marrow transplantation for them in a near future. Conclusion: Although is a well recognized clinical entity, invasive disease caused by aspergillus niger is less common when compared to aspergillus fumigatus and other Aspergillus species .These two case reports demonstrate the potentially aggressive nature of aspergillus niger and highlight the importance of looking for an immune deficiency particularly in the case of uncommon infection such as aspergillosis in early childhood.